PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP TINGKAT PENGUNGKAPAN RISIKO (Studi Empiris pada Perusahaan Nonkeuangan yang Terdaftar di Bursa Efek Indonesia) - Anindyarta Adi Wardhana; Nur Cahyonowati (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to analyze the effect of company characteristics such as ownership structure, independent nonexecutive director, audit committee independence, external auditor quality, firm size, leverage and industry type on the level of risk disclosure on all nonfinancial companies listed on the Indonesia Stock Exchange in 2011. This study is a replication of the research that has been done by Oliviera et al. (2011). However, control variable which are listing status and accounting standard that were used by Oliviera et al. (2011), are not being used in this research, because the variable is not applied in Indonesia. Financial companies are not used because they have different regulations with nonfinancial companies. This research is an empirical study with purposive sampling techniques in data collection with the following criterias: 1. Non-financial companies listed on the Indonesia Stock Exchange in 2011. 2. Completed annual reports published in 2011. The data obtained from annual report of 328 non-financial companies listed on the Indonesia Stock Exchange in 2011. Data were analyzed by Partial Least Square.The hypothesis in this research are as follows, 1. Concentrated ownership structure affects negatively on the level of risk disclosure, 2. Independent nonexecutive director affect positively on the level of risk disclosure, 3. Independent audit committees affect positively on the level of risk disclosure, 4. Big4 accounting firm engagement affect positively on the level of risk disclosures, 5. Leverage affects positively the level of risk disclosure, 6. Firm size affect positively on the level of risk disclosure, 7. High level of environmental sensitivity affect positively on the level of risk disclosure. The results from the test of hypothesis indicated that the size and quality of the company's external auditors are significantly influenced on the level of risk disclosure. Furthermore, the ownership structure, independent nonexecutive director, audit committee independence, leverage and industry type does not significantly influenced the level of risk disclosure. The result of this study provides information for investor about the risk that company could have, and also useful to give information for decision making.